2021
DOI: 10.3390/microorganisms9050916
|View full text |Cite
|
Sign up to set email alerts
|

Myxococcus xanthus as a Model Organism for Peptidoglycan Assembly and Bacterial Morphogenesis

Abstract: A fundamental question in biology is how cell shapes are genetically encoded and enzymatically generated. Prevalent shapes among walled bacteria include spheres and rods. These shapes are chiefly determined by the peptidoglycan (PG) cell wall. Bacterial division results in two daughter cells, whose shapes are predetermined by the mother. This makes it difficult to explore the origin of cell shapes in healthy bacteria. In this review, we argue that the Gram-negative bacterium Myxococcus xanthus is an ideal mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 108 publications
(176 reference statements)
0
6
0
Order By: Relevance
“…When spores germinate, emerging cells rebuild rod-shaped PG without preexisting templates 23 . Such morphological transitions make M. xanthus an ideal organism to study PG degradation and assembly 24 . The Rod system is essential for the de novo establishment of rod shape during M. xanthus spore germination 23 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…When spores germinate, emerging cells rebuild rod-shaped PG without preexisting templates 23 . Such morphological transitions make M. xanthus an ideal organism to study PG degradation and assembly 24 . The Rod system is essential for the de novo establishment of rod shape during M. xanthus spore germination 23 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous report on the purification of myxospores by heat treatment ( 17 ), it was shown that myxospores in distilled water often resist the heat treatment up to 58°C, while the majority of the contaminant does not. The intensity of frequency and duration of the exposure as the cardinal factors in the elimination of contamination and maintenance of myxospores, were determined for the myxospore of four myxobacterial genera in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Since myxospores do not germinate in nutrient-rich media in presence of fast growing heterotrophic bacteria, they can tolerate to the exposure of the toxicants such as antibiotics. The contaminants can be suppressed by the inhibitors of cell fission and the fruiting bodies are transferred into a suitable growth medium on which their myxospores can germinate without being affected by the fast growing contaminant cells ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to chemical signals, such as glycerol, vegetative cells of M. xanthus thoroughly degrade their PG and transform into spherical spores within two to four hours despite that the expression of the dacB gene is not regulated 20,[27][28][29][30] . If DacB also degrades PG during sporulation, glycerol-induced sporulation could provide a scenario where DacB is highly activated.…”
Section: The Inhibition or Absence Of Apbps Enriches Dacb At Cell Pol...mentioning
confidence: 99%